(untitled) (Collection of research papers «PROGRESSIVE TECHNIQUE AND TECHNOLOGIES OF FOOD PRODUCTION ENTERPRISES, CATERING BUSINESS AND TRADE», 2026)
In the food processing industry, as a rule, multi-component raw materials are used, but mainly only one main component is subject to extraction. This leads to the fact that only a small part of the raw material (15-30%) goes into the composition of the final product, and the rest is considered waste, which usually contains a significant amount of useful substances. Scientists and practitioners of the industry research the chemical composition of secondary raw materials, offer technologies for their use for the production of food products of increased biological value. The article presents the results of research into the possibility of using secondary raw materials for the processing of walnuts (membranes) in the technology of bakery products. It was established that the content of iodine in walnut membranes is 4200 μg/100 g, which is significant in view of the daily human need for this substance. The recipe for the bakery product "Vanilla Bun" was chosen as the control. Nut membrane powder was introduced at the stage of dough kneading after preliminary mixing with wheat flour. The additive was applied in the amount of 2.5; 5.0 and 7.5% of the weight of the finished product. It was established that the introduction of walnut membrane powder causes a slight deterioration of the dimensional stability of products, practically does not affect the porosity and moisture of bakery products, but contributes to the reduction of their losses during baking. The decrease in baking can be caused by the moisture-retaining properties of fiber and the possible formation of complexes of additive substances with dough components, which helps to reduce the loss of not only moisture, but also dry substances. All samples have acceptable organoleptic indicators, only in the sample with the highest content of the additive, a slight off-flavor appears and the shape deteriorates slightly. According to the results of the research, the recommended dosage of the additive in the technology of bakery products is 2.5 and 5% of the weight of the finished product. The iodine content in such products is 85.05 and 170.10 μg/100 g. Also, the proposed bakery product is characterized by lower calorie content and is significantly enriched with fiber.